GENEALOGI ALIRAN SYIAH - Asmaran As, Asmaran As (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2014)
This paper intends to address the emerging of Shiite genealogy in the history of Islamic thought. There are somequestion that needs to be asked: What is the Shiite? Furthermore, what is the background of the rise of the Shiite?As for the writer, Shiite is a group of Muslims who believe that the successor (khalifa) on leadership (Imamate) bothin the field of religion and politics after the Prophets death was Ali bin Abi Talib, cousin of Prophet Muhammadand his descendants were called Ahli bayt. There are several theories about the background of Shiite. Some said it iscaused by the privilege of Ali in comparating with the other prophets companion. Some said it is caused by theinfluence of non islamic cultural and religious teachings such as Persian and Jews. Some said it is caused by thepolitical conflicts in the Islamic community after the death of the Prophet. For the Shiites themselves believe that thequestion of replacement of the Prophet, that Ali bin Abi Talib, has got the legitimacy of both the Quran andHadith.